2009
DOI: 10.1093/hsw/34.3.179
|View full text |Cite
|
Sign up to set email alerts
|

Parent Mentoring and Child Anticipatory Guidance with Latino and African American Families

Abstract: Poor health and developmental outcomes for children are linked to scarcity of economic resources, various barriers in the delivery of health services, and inadequate parenting. To mitigate such adverse effects and address the needs of 50 high-risk, low-income Latino and African American families receiving well-baby care at an urban primary care health center, a collaborative team from the social work, nursing, and education fields piloted a preventive two-year parent mentoring project. The intervention was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
24

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(63 citation statements)
references
References 0 publications
1
38
0
24
Order By: Relevance
“…Eleven articles were identified through a reference search of accepted articles. Thirty-three articles were accepted; these included 13 articles primarily on alternative formats for WCC, 16,25-36 2 articles primarily on nonclinical locations for WCC, 37,38 17 articles primarily on nonphysicians/ non-NPs added to enhance WCC, 17,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] and 1 miscellaneous article. 55 Of 13 WCC format articles, 5 were on non-face-to-face formats, [25][26][27][28]36 and 8 were on group visit formats.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven articles were identified through a reference search of accepted articles. Thirty-three articles were accepted; these included 13 articles primarily on alternative formats for WCC, 16,25-36 2 articles primarily on nonclinical locations for WCC, 37,38 17 articles primarily on nonphysicians/ non-NPs added to enhance WCC, 17,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] and 1 miscellaneous article. 55 Of 13 WCC format articles, 5 were on non-face-to-face formats, [25][26][27][28]36 and 8 were on group visit formats.…”
Section: Resultsmentioning
confidence: 99%
“…16,[29][30][31][32][33][34][35] Of the 17 WCC provider articles, 13 articles and 1 systematic review reported on the Healthy Steps for Young Children Program (HS, which uses a developmental specialist in WCC), 17,39-51 2 articles reported on a study using a developmental specialist in another intervention, 52,53 and 1 reported on use of a parent coach. 54 The WCC location articles included 1 intervention of home WCC 37 and 1 for preschool-based WCC. 38 The miscellaneous article reported findings from an intervention that included a social worker in visits and so was placed in the provider category.…”
Section: Resultsmentioning
confidence: 99%
“…13,[36][37][38] In a recent review of tools and strategies to improve WCC, we found evidence suggesting that inclusion of nonphysician providers into a health care team could improve receipt of anticipatory guidance and developmental and behavioral services. 16,17,[39][40][41][42] In Healthy Steps, a physician and child developmental specialist (typically a nurse, social worker, or early childhood educator) provide WCC in partnership. In a large, national, 3-year trial, intervention parents reported receiving more anticipatory guidance and more family-centered care and were more likely to be up-to-date on WCC.…”
Section: Discussionmentioning
confidence: 99%
“…49 Some programs have been developed specifically to improve the delivery of preventive and primary care services for children in poverty. 16,[50][51][52][53] For example, the Parent-focused Encounters, Newborns to Toddlers Intervention, uses a health educator ("parent coach") to provide the bulk of well-child care (WCC) services. 16 At each visit, the parent coach provides anticipatory guidance; psychosocial screening/referral; and developmental and behavioral surveillance, screening, and guidance.…”
Section: Care Coordination Programsmentioning
confidence: 99%